Effect of Capital, Location, and Hours of Work on the Income of Surade Traditional Market Traders, Sukabumi Regency. - Afrizal Afrizal; Evi Martaseli; Iqbal Noor (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
This study aims to determine: 1. To explain how the influence of capital on the income of traders in the Surade market, Sukabumi Regency. 2. To explain the effect of location on the income of traders in the Surade market, Sukabumi Regency. 3. To explain the effect of working hours on the income of traders in the Surade market, Sukabumi Regency. 4. To explain the effect of capital, location, and working hours on the income of traders in the Surade market, Sukabumi Regency. Variables consist of capital, location and working hours as independent variables and trade income as dependent variable. This study uses quantitative methods. can be a research method based on the philosophy of positivism, used to examine the population as well as certain samples, sampling techniques are generally carried out randomly, data collection uses research instruments, quantitative/statistical data analysis aims to test the established hypothesis. The type of data used in this study is secondary data, namely data generated from the interview process and direct observation to the informants. Secondary data was obtained through the process of observation and interviews as well as data evidence in the form of documentation and data from the archives of the company where the research was carried out with consideration of previous research. the results of this study produce data that capital, trade location, working hours have a strong influence on trade income.